Sunrise reef [large type] - Hannon, Irene (Hannon, Irene. Hope Harbor (Series), 2025)
"After years of searching, Bren Ryan has found her place in Hope Harbor. Working as a barista suits her to a T, as does the laid-back vibe of her adopted town. Nothing is lacking in her life except romance. But that's okay. Men are a complication she doesn't need. Buttoned-up CPA Noah Ward isn't looking for love, either, when he arrives in town on a mission to convince his father to move closer to him. And he certainly doesn't intend to fall for the quirky, free-spirited woman who's taken up residence in his father's guest cottage. But when he finds himself sucked into her quest to help a struggling teen, might the two of them discover there's more to each other than meets the eye?"--